Perkembangan Organisasi Penyelenggara Lembaga Pendidikan Islam Yayasan Al-Ma'ruf Denpasar Tahun 2004 - 2020 - Pulungan, Dina Delda Sari; Jumari, Jumari; Muhayat, Imam (Faidatuna, 2021)
This research is motivated by the lack of complete information, both from books and religious study texts about the problems and developments of organizations that organize Islamic educational institutions, especially in Bali. Also, the uniqueness of the Denpasar Al-Ma'ruf Foundation was found from the preliminary study. The focus of this research is: 1) How is the development of the organization that organizes Islamic education institutions, the Al-Ma'ruf Denpasar Foundation in 2004–2020?; and 2) What are the obstacles faced and solutions made by the Al-Ma'ruf Denpasar Foundation, especially in the early days of its establishment?. The purpose of this study is to find out: 1) How is the development of the organization that organizes Islamic education institutions, the Al-Ma'ruf Denpasar Foundation in 2004–2020; and 2) What are the obstacles faced and solutions made by the Al-Ma'ruf Denpasar Foundation, especially in the early days of its establishment. This study uses descriptive qualitative methods, with data collection through observation, interviews, and documentation techniques. The results showed; 1) From the description of the research location, it proves the readiness, compliance, and accuracy of the foundation to the internal and external conditions of the foundation. In addition to experiencing such a rapid evolution, the Al-Ma'ruf Denpasar Foundation also experienced stagnation and involution in several of its activities, and 2) The biggest obstacles faced by the foundation, namely; provision of land and buildings, approval of permits from the environment, as well as the readiness of professional, qualified, and competent human resources. Solutions carried out by the foundation, namely; by renting land contracts, supporting funds from the foundation's business, persuasive approaches to the surrounding community and related officials, and asking for assistance from experts including teachers and staff from Java.